FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SAHAM PERUSAHAAN AGRIBISNIS DI BURSA EFEK JAKARTA: PENDEKATAN STRUCTURAL EQUATION MODELLING - ANTARA, MADE; INDAH LESTARI, PUTU (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008)
Capital Market is a market which is for many long term monetary instruments that can be sold and bought. The capital market has major functions for the economy system of a country because it functions for rising up the efficiency in an economy system by connecting money from investor to the company. This present research intended to know how much may effects of macro and micro in agribusiness company stock performance in Jakarta Stock Exchange, JSX (now: Indonesiaq Stock Exchange, ISE)). The location of this research was done by purposive sampling. The data was collected by using a study documentation which means learning some documents of much agribusiness company which was taken from JSX Monthly Statistics. The data was analysed by using Structural Equation Modelling (SEM) method which means by an integrated analysis, consist of correlation analysis (regression and correlation), the application of structural mode, path analysis, and factor analysis. The measure process will use the SPSS 12.0 for windows and Amos 4.01 program. By analysis the data, the result of it are the factor that effect the stock performance are macro and micro. Macro consists of exchange-rate, inflation, and interests. Micro consist Earning per Share (EPS), Net Profit Margin (NPM), Price Earning Ratio (PER), Rate Return of Investement (ROI), dan Return of Equity (ROE). Besides, the stock performance also affect the price of stock, devidend, and volume trade. Macro direclty affect the stock performance for 0,037. but micro affect the stock performance for 0,033. The investor who will invest their money in capital market need to care for the fluctuation of interest because, the interest has many effect based on the data analysis above. In micro, the investor need to care for the EPS value because the high EPS shows any probability will be higher in turn of invest.
Keywords: Capital Market, Jakarta Stock Exchange, Macro consists, Micro Consists